2008
DOI: 10.1016/j.physletb.2007.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Instability of agegraphic dark energy models

Abstract: We investigate the agegraphic dark energy models which were recently proposed to explain the dark energy-dominated universe. For this purpose, we calculate their equation of states and squared speeds of sound. We find that the squared speed for agegraphic dark energy is always negative. This means that the perfect fluid for agegraphic dark energy is classically unstable. Furthermore, it is shown that the new agegraphic dark energy model could describe the matter (radiation)-dominated universe in the far past o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(81 citation statements)
references
References 31 publications
1
79
0
1
Order By: Relevance
“…However, the perfect fluid of holographic DE with future event horizon is classically unstable because its squared speed is always negative [31] . Also in [32], it is shown that the agegraphic model of DE have a negative sound speed squared in flat, non-flat and also in the presence of interaction indicating the instability of this model against perturbations.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the perfect fluid of holographic DE with future event horizon is classically unstable because its squared speed is always negative [31] . Also in [32], it is shown that the agegraphic model of DE have a negative sound speed squared in flat, non-flat and also in the presence of interaction indicating the instability of this model against perturbations.…”
Section: Introductionmentioning
confidence: 92%
“…In this paper, we would like to generalize the approach presented in [28,31,32] to GDE model in a universe with spacial curvature in the presence of interaction between the dark matter and DE. Various aspects of GDE have recently investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In these two models, the IR cutoff length scale is given by the conformal time η and the average radius of the Ricci scalar curvature |R| −1/2 , respectively. There have been some numerical studies on these two models [574,586,587,588,589,590]. In general, these studies showed that the ADE and RDE models are not favored by current observations.…”
Section: Holographic Dark Energy Modelsmentioning
confidence: 99%
“…Hence we expect that for the present and future dark energy-dominated universe, the EOS is reduced to that of new agegarphic dark energy model as [30,31,32,52] …”
Section: New Agegraphic Dark Energy Model With Gupmentioning
confidence: 99%